Chemical looping oxidation of CH4 with 99.5% CO selectivity over V2O3‐based redox materials using CO2 for regeneration. Issue 1 (9th September 2019) - Ge, Yuanzheng; He, Tao; Wang, Zhiqi; Han, Dezhi; Li, Jianqing; Wu, Jingli; Wu, Jinhu
Abstract: The main challenge of chemical looping dry reforming of methane (CLDRM) is the development of a high‐performance redox material. In this study, V2 O3 was proved to be a unique redox material possessing high oxygen storage capacity (421.6 mg/g‐V2 O3, CH4 consumption base) and strong carbon‐deposition suppressing capability. It can be reduced to carbide by CH4, and the carbide can be reoxidized to V2 O3 with CO2 . Based on this redox cycle, CH4 conversion with 99.5% CO selectivity coupled with efficient CO2 splitting to CO was realized successively. However, the CH4 conversion over pristine V2 O3 is low (<50%) and not stable, therefore catalytic activation of C‐H bonds combined with structural modification of V2 O3 was carried out to accelerate the stoichiometric reactions and improve the redox stability. Finally, a maximum CH4 conversion of 81.7% with stable performance during cycles was reached, and further investigation confirmed the series reaction mechanism and identified the rate‐controlling step.